Efficacy of a Gel from the Seed of Trigonella foenum-graceum L. in Preventing Trichoptilosis: A Randomized Placebo-Controlled Clinical Trial - Majid Hajizadeh; Mohammad Azadbakht; Hossein Asgarirad; Ghasem Rahmatpour Rokni; Moloud Fakhri; Fatemeh Mirzaee (Journal of Mazandaran University of Medical Sciences, 2022)
Background and purpose: Trichoptilosis with fragility and hair loss is a common disorder, but, still there is no specific and effective treatment for this condition. The aim of this study was to evaluate the efficacy of gel from the seed of Trigonella foenum-graceum L. in prevention of trichoptilosis in people with trichoptilosis. Materials and methods: A double-blind placebo controlled clinical trial was carried out in 60 people with trichoptilosis in Sari Touba Clinic affiliated with Mazandaran University of Medical Sciences. The participants received either T. foenum-graceum seed gel or placebo gel. The extract was prepared at 500 μg/ml and the treatment period was two months. Data were analyzed using Independent t-test, Paired t-test, Fisher's exact test, and Generalized estimating equations. Results: In this study, the average rate of hair splitting in experimental group decreased significantly compared with the placebo group (P<0.001). Other factors such as dryness, fragility, and hair loss showed considerable decreasing rate in experimental group compared to the placebo group (P≤0.001, P<0.001, and P=0.042, respectively) Conclusion: The positive effects of the herbal gel in reducing the incidence of trichoptilosis may probably be due to the presence of diosgenin and other steroidal saponins with antioxidant and anti-inflammatory effects.